Emotion-focused therapy for grief and bereavement - Sharbanee, Jason; Greenberg, Leslie (Taylor & Francis, 2022)
We present an Emotion Focused Therapy perspective on working with grief and bereavement. This perspective considers emotions as a fundamentally adaptive signaling system that provides people with important information about their needs and goals. Thus the focus in working with grief and bereavement in EFT is to access and symbolize people’s adaptive grief around their loss. When this grief is blocked by other emotional states, such as lingering resentments, guilt, or fear of emotional pain, it is important for these other emotions to also be accessed and differentiated from the grief. This emotional processing can be facilitated through an empathic relational stance and experiential interventions which are guided by emotion theory and process diagnosis.